The Determinant of Tax Compliance in Indonesia (Experience in E-Commerce Environment) - Sulastri, Sulastri; Andesto, Ronny; Oktris, Lin (Journal Research of Social Science, Economics, and Management, 2023)
The characteristics of e-commerce transactions that are fast, cross national borders, and present business model innovations that are increasingly developing raise new challenges in terms of taxation. The purpose of this research is to investigate the influence of the self-assessment system, tax socialization, and tax administration modernization on tax awareness and its implications for taxpayer compliance. The population in this study consists of taxpayers engaged in online trading (e-commerce). The data analysis technique employed in this research is quantitative, utilizing the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings of this study indicate that the self-assessment system has a significant impact on tax awareness, tax socialization significantly affects tax awareness, and tax administration modernization has a significant influence on tax awareness. Furthermore, the self-assessment system significantly influences taxpayer compliance, tax socialization has a significant impact on taxpayer compliance, and tax administration modernization significantly affects taxpayer compliance. The study concludes that higher levels of self-assessment system, tax socialization, and tax administration modernization lead to increased tax awareness. Additionally, as tax awareness levels increase, taxpayer compliance also tends to rise.